(untitled) (Veterinary Science, 2017)
The humor vitreous is a transparent and gelatinous substance, composed primarily of water, which is located in the cavity of the eye behind the lens, in the case of an avascular area and closed. In veterinary medicine, the postmortem analysis of the biological liquid can be used to identify various types of metabolic diseases, kidney and nutrition..The objective of the present work was to characterize the vitreous equine by determining its density, viscosity and surface tension, the concentration of protein, Na, K, P,Ca and Mg.Vitreous humor was obtained from healthy horse, killed in the Fridge Indio Pampa.The density was quantified from the method of pycnometer; rheological behaviour was studied using the digital rotary viscometer HAAKE, RS 600, and surface tension tension by the method of the ring from tensiometer Du Noüy. Total proteins were determined by means of a quantitative colorimetric method, technique PROTI U/LCR (Weiner LAB.) at same that contents of P (technique Fosfatemia (Weiner LAB); while the contents of Ca and Mg were determined by atomic absorption spectrometry and its of Na and K, by flame photometry. Results obtained for density, viscosity and surface tension were 1.0025 g.cm-3, 2.13 cp y 51.0045 dinas.cm-1, respectively and showed a good linear correlation with respect to temperature. Protein contents, P, Na, K, Ca and Mg were 0.033 g.dl-1, 1.1200 g. dl-1 , 151.82 mEq.l- 1, 3.7200 mEq.l-1, 3.2125 mgs dl-1 and 1.5379 mgs dl-1, respectively. One can conclude that after the postmortem characterization of this organic fluid, it may infer the state of health of the horses antemortem.